Sero-epidemiological assessment of Chlamydia trachomatis infection and sub-fertility in Samoan women. Issue 1 (December 2016) - Menon, S.; Stansfield, S.; Walsh, M.; Hope, E.; Isaia, L.; Righarts, A.; Niupulusu, T.; Temese, S.; Iosefa-Siitia, L.; Auvaa, L.; Tapelu, S.; Motu, M.; et al.
Abstract Background In our recent village-based cross-sectional study, the prevalence of nucleic acid amplification technique (NAAT) diagnosedChlamydia trachomatis (CT) in sexually active Samoan women was very high (36 %), and test positivity was associated with sub-fertility. We conducted a serological and epidemiological analysis in these participants to identify if serological data can provide further insight into the potential contribution of CT to sub-fertility in this population. Methods Serological prediction of CT associated sub-fertility was conducted using a series of commercial tests. The correlation between fertility or sub-fertility, behavioral factors, and serologically predicted CT associated sub-fertility was determined. Results A positive antibody reaction against theChlamydia Major Outer Membrane Protein (MOMP) was significantly associated with sub-fertility, with 50 % of infertile women being positive. Serum IgG and IgA antibodies against MOMP correlated with current infection measured by urine NAAT, suggesting longer term infections are common in this population.Chlamydia pneumoniae antibodies were frequently detected in this population (84 %), and unexpectedly, were significantly associated with sub-fertility. Conclusions The high prevalence of chlamydial infection and of positive chlamydial sub-fertility results suggests that CT is an important and frequent contributory factor to sub-fertility in this population.